The Dynamics of the Balinese Literature in the Present Day Bali - I Ketut Ardhana, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Balinese literature has a significant role in the context of how theBalinese have preserved their own cultural tradition up to now.Even though the Majapahit Kingdom in the fourteenth centurystrongly influenced the Balinese tradition in the past, but itseems that the Balinese recently also look back at their culturaltradition prior to the period of the Majapahit influence. There aresome crucial issues in relation to the above explanation: firstly,there have been widely debated on the issue around the originof the Balinese tradition. On the one hand scholars argue thatthe origin of Balinese tradition is not started from the East Javaperiod, but it was earlier than that it had been started prior tothe period of the Majapahit such as the Middle Java period inthe 8th to 9th century or, even, in the West Java Hindu traditionthat also played a major role. However, others have not convincedwith this argument; Secondly; due to globalization process, theBalinese perceive that the only way to anticipate the impacts ofglobalization is just to revitalize the local Balinese cultures byseeking at the Balinese literatures as the local sources like thebabad, paswara, and awig-awig; Thirdly; to counter the negativeimpacts of globalization, the Balinese use their local culturalheritage so that they can maintain their cultural tradition thatnot based on Balinese tradition, but also the Javanese tradition. Itis important to discuss such issue since the influences of pre andpost Majapahit cultural traditions have indeed influenced thecultural identity of the Balinese. On top of this, to understandthe concept of multiculturalism in the present day Bali, oneneeds to trace back the dynamic of interplay amongst arrays ofcultural traditions that have affected the origin of multiculturalsociety there
Keywords: Balinese literature; babad; paswara; awig-awig; cultural heritage